The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11547-016-0644-3
|View full text |Cite
|
Sign up to set email alerts
|

Foci on breast magnetic resonance imaging in high-risk women: cancer or not?

Abstract: PurposeTo assess how frequently foci are identified on MRI in high-risk patients, and their association with malignancy, breast density, and background parenchymal enhancement (BPE).Materials and methodsIn this multicentric study, two readers, in consensus, retrospectively reviewed screening breast MRI of 245 high-risk women, performed between 2009 and 2014. Eligible patients had at least two consecutive screening MRI, and a follow-up of at least 1 year after a lesion was first detected; histology was availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Thus, the characterization of nonmass enhancement and foci is important. However, a standardized classification scheme for the interpretation of lesions showing nonmass‐like enhancement does not exist, and the best management of foci remains under discussion 5,38 . In the future, we would like to continue investigating the utility of synthetic MRI to differentiate benign from malignant lesions in patients with nonmass enhancement and foci.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the characterization of nonmass enhancement and foci is important. However, a standardized classification scheme for the interpretation of lesions showing nonmass‐like enhancement does not exist, and the best management of foci remains under discussion 5,38 . In the future, we would like to continue investigating the utility of synthetic MRI to differentiate benign from malignant lesions in patients with nonmass enhancement and foci.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the lesions was defined as a focus, and the mean lesion size was relatively large, we did analyze lesions in the range of 3-10 mm separately and we found that size can reduce the sensitivity of MRI. Foci were either classified as BPE, or as BI-RADS 3, and sent to control due to the low rate of malignancy for foci (28). As only histologically verified lesions were included in our analysis, no focus was included in the study.…”
Section: Sensitivity Specificitymentioning
confidence: 99%
“…might be difficult to further characterise. These small findings were defined by the American College of Radiology Breast Imaging Reporting and Data System (BI-RADS) as enhancing foci [7]. Depending on the spatial resolution, it is difficult to evaluate their morphology and dynamic behaviour, while the small size makes difficult to perform MRI-guided needle biopsy, so that their changes are commonly longitudinally monitored with serial examinations to reach a conclusive diagnosis [8].…”
mentioning
confidence: 99%